2003
DOI: 10.1103/physrevb.68.014434
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation inCu90Co10high-magnetoresistance materials

Abstract: The relation between giant magnetoresistance ͑GMR͒ and phase separated nanostructures in Cu 90 Co 10 is studied using magnetotransport measurements together with transmission electron microscopy and x-ray microanalysis. The samples were melt-spun ribbons isochronally annealed up to 873 K, and all show in their grains a homogeneous spinodal decomposition characterized by long parallel Co-excess stripes. These stripes have 40-nm modulation periods and develop along the crystalline directions of each grain. Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
44
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 40 publications
7
44
1
Order By: Relevance
“…In addition, it has been shown that in Cu90Co10 alloys, a spinodal type decomposition of the formed supersaturated solid solutions occurs after annealing at elevated temperatures [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it has been shown that in Cu90Co10 alloys, a spinodal type decomposition of the formed supersaturated solid solutions occurs after annealing at elevated temperatures [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Below 400°C the solubility of Co in Cu (and vice versa) is negligible [28]. Homogeneous Cu-Co alloys with supersaturations far from equilibrium can be produced by ball milling [29,30], sputtering [31], melt-spinning [32] and rapid quenching [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is fascinating that the spontaneously formed periodic structure influences the band gap, transport, and optical properties of the semiconductor alloys [6]. Additionally, periodically formed ferromagnetic alloys after SD wherein a magnetically ordered phase is embedded in a non-magnetic matrix is a very promising structure for device applications because giant magnetoresistance and other collective properties were observed, and thus has important implications for device design [6–8]. SD is a general phenomenon observed in various systems, such as alloys, glasses, and oxides.…”
Section: Introductionmentioning
confidence: 99%